Energetic, structural and dynamic evaluation of HIV-1 proteases - Naicker, Previn (My University, 2015)
Human immunodeficiency virus (HIV), the causative agent of the acquired immunodeficiency syndrome (AIDS), remains a topic of global concern even though great strides have been made to combat the virus. The high replicative rate of the virus and recombination of the variety of viral strains complicate the treatment of AIDS. There has been an increasing prevalence of African HIV strains in the Americas and Europe. The viral protease (PR) is vital for the propagation of the virus; and thus, is a major target in antiviral therapy. The HIV-1 PR enzyme from the subtype C strain; which predominates in sub- Saharan Africa, has been greatly under-investigated in comparison to the protease from the subtype B strain which predominates in North America and Europe. Enzyme activity data which were part of this work suggested that the South African HIV-1 subtype C protease (CSA PR) displays improved substrate turnover in comparison to the subtype B PR. Thermodynamics and inhibition kinetics of drug binding showed that the C-SA PR is less susceptible to certain clinically-used protease inhibitors when compared to the subtype B PR. A crystal structure of the C-SA PR was solved and showed no difference to the global structure of the subtype B PR. Molecular dynamics simulations showed that the C-SA PR exhibits a wider range of open conformations. Hydrogen/deuterium exchange-mass spectrometry (HDX-MS) was performed to elucidate the mechanism of reduced drug susceptibility displayed by the C-SA PR. HDX-MS data provided insights into the basis of the increased preference for open conformers displayed by the C-SA PR and the stability of the terminal dimer interface which is a target in protease inhibition.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. August 2014.
Keywords: Proteolytic enzymes.; HIV (viruses); AIDS (Diseases)